159: DEFINITIVE CHEMORADIOTHERAPY VERSUS NEOADJUVANT CHEMORADIOTHERAPY FOLLOWED BY RADICAL SURGERY FOR LOCALLY ADVANCED ESOPHAGEAL SQUAMOUS CELL CARCINOMA: SYSTEMATIC REVIEW AND META-ANALYSIS. (23rd April 2022) - Kamarajah, S K; Evans, R; Gossage, J; Griffiths, E; Pucher, P
Abstract: Background and aim: Debate exists surrounding definitive chemoradiotherapy (dCRT) over neoadjuvant chemoradiotherapy and surgery (nCRS) as a primary treatment for esophageal squamous cell carcinoma (ESCC) owing to the heterogeneity in the quality of current evidence. This study aimed to compare long-term survival of dCRT with nCRT for ESCC from high-quality studies. Methods: This systematic review was performed according to PRISMA guidelines and eligible studies were identified through a search of PubMed, Scopus and Cochrane CENTRAL databases up to 23rd July 2021. Primary outcome was overall survival (OS) and secondary outcomes were disease-free survival (DFS) and recurrence rates. A meta-analysis was conducted using random-effects modelling to determine pooled adjusted multivariable hazard ratios (HRs). Results: This review included ten high-quality studies including 14, 092 patients, of which 30% received nCRT. Three studies were randomized controlled trials (RCT), six studies were single-center. dCRT and nCRT regimens were reported in six studies and surgical quality control were reported in two studies. Outcomes for OS and DFS were reported in eight and three studies, respectively. nCRT had significantly longer OS (HR: 0.68, CI95%: 0.54–0.87, P < 0.001) and DFS (HR: 0.50, CI95%: 0.36–0.70, P < 0.001) than dCRT. Conclusion: nCRS followed by planned esophagectomy appears to remain the optimum curative treatment regime in patients with loco-regional ESCC. Thus, surgery remains an integral component of the management of patients with ESCC. As adjuvant and immunotherapy treatment regimens develop, ongoing prospective assessment of the role of radiotherapy in combination with modern treatment modalities should be studied.